2002
DOI: 10.1086/345724
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Histoplasmosis in Patients with Acquired Immunodeficiency Syndrome in the United States and Brazil

Abstract: Demographic and clinical parameters among patients with acquired immunodeficiency syndrome and histoplasmosis in Brazil and United States were compared. The Brazilian isolates were typed by restriction-fragment length polymorphism analysis and were DNA fingerprinted by random amplification of polymorphic DNA (RAPD)-polymerase chain reaction (PCR). Skin lesions occurred in 66% of Brazilian case patients, compared with 1%-7% of US case patients. Of 21 treated case patients, 4 (19%) died, a rate similar to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(86 citation statements)
references
References 23 publications
8
73
2
3
Order By: Relevance
“…The high mortality rate (40.0%) found in the 25 HIVpositive patients in the present study was similar to that reported in the study by KARIMI et al 5 . These high mortality rates reinforce the importance of an early and precise laboratory diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…The high mortality rate (40.0%) found in the 25 HIVpositive patients in the present study was similar to that reported in the study by KARIMI et al 5 . These high mortality rates reinforce the importance of an early and precise laboratory diagnosis.…”
Section: Discussionsupporting
confidence: 92%
“…It should be noticed that skin lesions are seldom observed in North American patients (8,9). Virulence and tropism of the isolates predominant in the sub-continents may explain these differences (8) although late diagnosis in Latin American countries may also explain the more extensive dissemination observed in these patients.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Disseminated histoplasmosis was later included in the list of opportunistic infection defining AIDS. Despite the increased use of highly active antiretroviral therapy (HAART), histoplasmosis remains an important opportunistic infection among HIV patients in endemic areas and frequently appears as the first manifestation of HIV infection or as the AIDS-defining illness (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…8 In developing countries and in some regions of the United States that include resource-poor areas, high mortality rates are reported for PLWHA who have progressive disseminated histoplasmosis (PDH). [9][10][11][12][13][14][15][16][17][18][19][20] For these reasons, health-care providers should be aware of the incidence of histoplasmosis in Colombia, and consider the possibility of this diagnosis in PLWHA patients with clinically compatible illness.…”
Section: Introductionmentioning
confidence: 99%
“…5,8,21,22 Histoplasmosis is a common and important public health problem in these susceptible populations. [9][10][11][12][13][14][15][16][17][18][19][20] The aim of this study was to identify a clinical and laboratory profile associated with histoplasmosis in PLWHA that could allow early suspicion of the disease, reducing the time to diagnosis and thus the disease's high mortality rate.…”
Section: Introductionmentioning
confidence: 99%